Association of Physical Fitness Performance Tests and Anthropometric Indices in Taiwanese Adults - Chen, Po-Hung; Chen, Wei; Wang, Cheng-Wei; Yang, Hui-Fei; Huang, Wan-Ting; Huang, Hsiu-Chen; Chou, Che-Yi (Frontiers in Physiology, 2020)
Background The association between physical fitness performance tests and anthropometric indices is not clear. The study aims to explore the association of physical fitness performance and anthropometric indices in Taiwan adults. This may help to monitor anthropometric indices to improve physical fitness. Methods We recruited 2216 participants aged 23-64 years between 2014 and 2017. Physical fitness performance including abdominal muscular endurance (60-second sit-up test), flexibility (sit-and-reach test), and cardiorespiratory endurance (3-min step test) was performed in all participants. The association of the physical fitness performance and anthropometric indices including body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR) was analyzed using linear regression with adjustments for age and gender. Results BMI was negatively associated with abdominal muscle endurance (p < 0.001) and cardiorespiratory endurance (p < 0.001). None of BMI, WC, WHR, and WHtR was significantly associated with flexibility. Abdominal muscle endurance, flexibility, and cardiorespiratory endurance were significantly lower in obese participants when obesity was defined using a BMI of ≥ 27, 30, and 35 kg/m2. Participants with central obesity that was defined as WC ≥ 90 cm in men and 80 cm in women and WHtR ≥ 0.6 had lower abdominal muscular endurance than those without central obesity. Conclusions BMI is associated with abdominal muscle endurance and cardiorespiratory endurance in Taiwan adults. None of the anthropometric indices are significantly associated with flexibility. Adults with obesity defined by BMI had significantly worse physical fitness performance than those without obesity.